Smallest acyclic tricationic molecule containing a Bis(phosphine)-stabilized low-valent triantimony-based Unit - Mukherjee, Nilanjana; Peerless, Benjamin; Nadurata, Vincent L.; Kumar, Vikas; Sangole, Mayur P.; Singh, Kirandeep; Wiedemann, Haakon T. A.; Kay, Christopher W. M.; Kruk, Robert; Weigend, Florian; Dehnen, Stefanie; Gonnade, Rajesh G.; et al. (Nature Communications, 2026)
Element-element bonded multiply charged cationic species are well known as dimers or small cyclic oligomers in the condensed phase. However, the smallest acyclic version, a trinuclear unit possessing greater than a monocationic charge, has remained elusive. Here we introduce a bis(phosphine) supported low valent triantimony-based tricationic compound as a new entrant in this field. Structural elucidation and electronic understanding reveal a W-shaped tricationic unit comprising of a three-center four-electron sigma-bonded triantimony moiety that is terminally capped by bis(phosphine) ligands, with the central antimony atom having two lone pairs of electrons. The unique counter trianion [Sb(O)2(OTf)4]3- (OTf = CF3SO3) possesses reactive polar Sb delta+-O delta- bonds, the structure of which is determined from single crystal X-ray diffraction analysis. The ensemble of reactive molecular fragments found in this highly charged antimony-based compound makes it thermally unstable. Nonetheless, this fully characterized fleeting species shows a diverse reactivity profile, advancing the isolation of various novel antimony compounds, including the formation of a distinct low-valent antimony-cobalt carbonyl cluster.